School Was Our Life : Remembering Progressive Education - Martin, Jane Roland, 1929- (Book collections on Project MUSE., 2018)
"The late 1930s and early 1940s was the peak of progressive education in the United States, and Elisabeth Irwin's Little Red School House in New York City was iconic in that movement. For the first time, stories and recollections from students who attended Little Red during this era have been collected by author Jane Roland Martin. Now in their late eighties, these classmates can still sing the songs they learned in elementary school and credit the progressive education they loved with shaping their outlooks and life trajectories. Martin frames these stories from the former students "tell it like it was" point of view with philosophical commentary, bringing to light the underpinnings of the kind of progressive education employed at Little Red and commenting critically on the endeavor. In a time when the role of the arts in education and public schooling itself are under attack in the United States, Martin makes a case for a different style of education designed for the defense of democracy and expresses hope that an education like hers can become an opportunity for all"--